2013
DOI: 10.1088/1367-2630/15/3/033016
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of frozen moments in the NiFe/FeMn exchange bias system

Abstract: We detect the presence of frozen magnetic moments in an exchange biased NiFe ferromagnet at the NiFe/FeMn ferromagnet/antiferromagnet interface by magnetic circular dichroism in x-ray absorption and resonant reflectivity experiments. Frozen moments are detected by means of the elementspecific hysteresis loops. A weak dichroic absorption with unidirectional anisotropy can be linked to frozen magnetic moments in the ferromagnet. A more pronounced exchange bias for increasing the thickness of the FeMn layer corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This is true for all of the FeMn thicknesses measured. This model of interfacial layers agrees with previous reports of uncompensated spins at the FM/AF interfaces by PNR measurements 4245 , and by x-ray techniques 46,47 in a variety of systems, such as Co/FeF 2 42 , Py/CoO 46 , NiFe/FeMn 47 . From our subsequent analysis we see that these uncompensated moments are not frozen and are able to rotate with applied field.…”
Section: Polarized Neutron Reflectivitysupporting
confidence: 92%
“…This is true for all of the FeMn thicknesses measured. This model of interfacial layers agrees with previous reports of uncompensated spins at the FM/AF interfaces by PNR measurements 4245 , and by x-ray techniques 46,47 in a variety of systems, such as Co/FeF 2 42 , Py/CoO 46 , NiFe/FeMn 47 . From our subsequent analysis we see that these uncompensated moments are not frozen and are able to rotate with applied field.…”
Section: Polarized Neutron Reflectivitysupporting
confidence: 92%
“…Brück et al showed that in a MnPd/Fe exchange-bias bilayer, the NS Mn moments extend into MnPd about 13Å [33]. More recently, Mohanty et al observed that in a NiFe/FeMn bilayer, the NS moments exist in both FM and AFM layers [34]. In the case of our polycrystalline Py/CoO system, the NS moment per unit area is estimated to be +4.9 × 10 −6 emu/cm 2 , which has the same order of magnitude as the estimate from the hysteresis loop measurement.…”
Section: A Polycrystalline Filmmentioning
confidence: 99%
“…Although experimental techniques, such as nuclear magnetic resonance and neutron diffraction, have been adopted to identify the antiferromagnetism and magnetic structures of AFM [9,10], they are constrained by the sample thickness, which should be thick enough to generate visible signals. Besides the earlier theories of exchange bias that focused on the interface of FM/AFM [11], x-ray magnetic linear dichroism (XMLD) and x-ray magnetic circular dichroism (XMCD) are preferable to detect the arrangement of interfacial spins simultaneously in FM and AFM, taking advantage of the element specificity and shallow probing depth for the total electron yield (TEY) mode [12][13][14][15]. Nevertheless, previous XMLD experiments were generally focused on the collinear AFM, such as NiO and FeRh [3,13], regardless of the noncollinear AFM, due to their complex spin axes.…”
mentioning
confidence: 99%